1999
DOI: 10.1016/s0304-3959(99)00106-2
|View full text |Cite
|
Sign up to set email alerts
|

Generalised muscular hyperalgesia in chronic whiplash syndrome

Abstract: The whiplash syndrome has immense socio-economic impact. Despite extensive studies over the past years, the mechanisms involved in maintaining the pain in chronic whiplash patients are poorly understood. The aim of the present experimental study was to examine the muscular sensibility in areas within and outside the region involved in the whiplash trauma. Eleven chronic whiplash patients and 11 sex and age matched control subjects were included in the study. Before the experiment, the whiplash patients had pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
90
2
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(115 citation statements)
references
References 16 publications
21
90
2
2
Order By: Relevance
“…This eccentric muscle contraction mechanism is consistent with the delayed onset of muscle symptoms observed in whiplash injuries [14,15]. This mechanism also supports the generalized muscular hyperalgesia present in subjects who have experienced whiplash trauma; this generalized central hyperexcitability might be caused through tissue injury [5].…”
Section: Discussionsupporting
confidence: 80%
“…This eccentric muscle contraction mechanism is consistent with the delayed onset of muscle symptoms observed in whiplash injuries [14,15]. This mechanism also supports the generalized muscular hyperalgesia present in subjects who have experienced whiplash trauma; this generalized central hyperexcitability might be caused through tissue injury [5].…”
Section: Discussionsupporting
confidence: 80%
“…A number of studies have shown central sensitization to be responsible for sensory threshold changes and widespread tenderness, as well as peripheral sensitization (13,14,33). Tissue damage stimulates the release of numerous inflammatory mediators from neurons and immune cells (34), resulting in activation of nociceptors in the injury area and nociceptor hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Increased nociceptor sensitivity is expressed by spontaneous firing, enlargement of the neuronal receptive field, and decreased firing threshold (35,36), which is known as the peripheral sensitization-an initiative for pain. Effective changes in tissue sensitivity may develop immediately after injury and the resultant pain because of neurobiological influences (14,37). Then, they may be followed by pain in unrelated sites and persistent exaggerated pain outside of the neuro-anatomical sensory distribution of the primary lesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The particular injury producing persistent WAD is still, however, not well known, c.f. Johansen et al (1999). 1 A discussion about the existence of chronic WAD is going on in the medical literature, with some researchers attributing chronic disorders to specific injuries and others sceptical towards the existence of persistent WAD (Livingston 2000).…”
Section: Introductionmentioning
confidence: 99%